Multifunctional polyacrylonitrile‐ZnO/Ag electrospun nanofiber membranes with various ZnO morphologies for photocatalytic, UV‐shielding, and antibacterial applications. Issue 4 (24th October 2014) - Chen, Yen‐Yu; Kuo, Chi‐Ching; Chen, Bo‐Yu; Chiu, Pei‐Chi; Tsai, Ping‐Chun
ABSTRACT New multifunctional polyacrylonitrile (PAN)‐ZnO/Ag composite electrospun nanofiber membranes consisting of pineal‐type, flower‐type, and sea‐urchin‐type ZnO morphologies were prepared using a single‐capillary electrospinning technique, hydrothermal ZnO synthesis, and Ag reduction. The various ZnO architectures exhibited differences in photocatalytic activity and UV‐shielding efficiency, and were ranked as follows: sea‐urchin type > flower type > pineal type. Sea‐urchin‐type ZnO features a higher surface‐to‐volume ratio than other ZnO architectures do because of its distinctive structure, thus yielding higher performance. The present study demonstrated that self‐standing PAN‐ZnO/Ag composite fiber membranes, especially those with the sea‐urchin‐type ZnO structure, can be applied in multifunctional textiles such as water purification filters and antibacterial and UV‐shielding clothes. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 262–269